Identification and analysis of mitochondria-related central genes in steroid-induced osteonecrosis of the femoral head, along with drug prediction - Ma, Zheru; Sun, Jing; Jiang, Qi; Zhao, Yao; Jiang, Haozhuo; Sun, Peng; Feng, Wei (Frontiers in Endocrinology, 2024)
Purpose: Steroid-induced osteonecrosis of the femoral head (SONFH) is a refractory orthopedic hip joint disease that primarily affects middle-aged and young individuals. SONFH may be caused by ischemia and hypoxia of the femoral head, where mitochondria play a crucial role in oxidative reactions. Currently, there is limited hormone-related ischemic necrosis of the femoral head (SONFH) was confirmed using ROC curves.Conclusions: BID, FTH1, LACTB, PDK3, RAB5IF, SOD2, and SQOR may serve as potential diagnostic mitochondrial-related biomarkers for SONFH. Additionally, they hold research value in investigating the involvement of mitochondria in the pathogenesis of ischemic necrosis of the femoral head.